The Calern Asteroid Polarimetric Survey using the Torino polarimeter: assessment of instrument performances and first scientific results. Issue 4 (26th December 2016) - Devogèle, M.; Cellino, A.; Bagnulo, S.; Rivet, J. P.; Bendjoya, P.; Abe, L.; Pernechele, C.; Massone, G.; Vernet, D.; Tanga, P.; Dimur, C.
Abstract: A new polarimeter based on the wedged double Wollaston concept has been built at the Torino Observatory and installed on a 1-m telescope at the Calern observing station of the Observatoire de la Côte d'Azur, France. Its main purpose is to carry out a polarimetric survey of minor Solar system objects, which is called the Calern Asteroid Polarimetric Survey. In this paper, we describe the new Torino polarimeter and the results of preliminary scientific validation tests. A number of standard stars with known polarization states, as well as a number of asteroids for which the polarimetric properties are known, have been observed in order to assess the instrument's accuracy. The instrumental polarization has been found to be stable within a few 10 −4 units. A total of 124 new polarimetric observation of 78 asteroids are presented. In the case of asteroids already observed in the past, the new data are in agreement with available phase–polarization curves with error bars smaller than most previously published data. We also present data for 21 asteroids that have never been observed before in polarimetry.